2019
DOI: 10.1002/jor.24551
|View full text |Cite
|
Sign up to set email alerts
|

Computational Model Validation of Contact Mechanics in Total Ankle Arthroplasty

Abstract: Revision rates in total ankle arthroplasty (TAA) are nearly double compared with hip or knee arthroplasty procedures. Contact mechanics for metal-polyethylene articulation in TAA is critical due to the reduced size of the implant and higher expected load, compared with a hip or knee joint. This study was focused on developing a validated computational model to predict contact area in a polyethylene tibial bearing articulating with a metallic talar component in a bicondylar TAA design. Contact area was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Comparatively, the difference percentage of the contact area and average contact stress from measurements of Fuji film and simulated FE analysis displayed as 1.94% and 29.21%, respectively. Previous studies revealed the accuracy of Fuji film techniques assessed the contact stress distribution of the TKA displayed in a range of 6 % to 36% [30], [33]. Although the Fujifilm technique was variable, the significant advantage has been reviewed numerous times and is satisfied with various applications [34].…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, the difference percentage of the contact area and average contact stress from measurements of Fuji film and simulated FE analysis displayed as 1.94% and 29.21%, respectively. Previous studies revealed the accuracy of Fuji film techniques assessed the contact stress distribution of the TKA displayed in a range of 6 % to 36% [30], [33]. Although the Fujifilm technique was variable, the significant advantage has been reviewed numerous times and is satisfied with various applications [34].…”
Section: Discussionmentioning
confidence: 99%
“…The latter part of the procedure, in particular, the verification and validation, specifically helps address the accountability and transparency of models. Verification is ensuring that the model is implemented correctly, and that the model accurately captures a conceptual description of the problem of interest. , Validation is the process of establishing the degree to which a model is an accurate representation of the real world for its intended purpose. In other words, a model does not fail a validation process, but instead provides information about the acceptability or trustworthiness of the predictions from the model . In addition to aiding in the accountability of the models, the ten rule framework helps streamline the wide range of modeling approaches to complex problems.…”
Section: Introductionmentioning
confidence: 99%